Locally manufactured wheelchairs in Tanzania : Do they meet the needs of Tanzanian wheelchair users? - Ndosi, Aston (Department of Health and Rehabilitation Sciences, 2015)
Access to suitable wheelchairs may seriously impact the ability of people with physical disabilities to integrate into regular community life. The overall aim of this study was to determine the extent to which the needs of users of wheelchairs manufactured locally in Tanzanian are met. The specific objectives of the study were to determine users' satisfaction with the wheelchairs manufactured in Tanzania, their satisfaction with services associated with the provision, repair and maintenance of these wheelchairs, and the extent to which these wheelchairs enabled them to carry out their daily activities. A quantitative descriptive cross-sectional study was carried out among 75 users of locally manufactured manual wheelchairs, aged 18-65 years and residing in Dar es Salaam, Arusha and the Kilimanjaro regions of Tanzania. Data was collected using a questionnaire consisting of demographic items and two existing instruments, the Functioning Everyday with a Wheelchair (FEW) and Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST) 2.0. Data were analysed with the Statistical Package for the Social Sciences (SPSS) software program version 20.0. Descriptive analysis was performed using frequencies and proportions for categorical data or median and ranges for numerical data. The chi-square test was conducted to determine whether there were significant difference between gender and place of residence (rural/urban) and satisfaction with functional needs, wheelchair and activity and participation.